Hemifacial Hyperplasia - A Case Report - Sanjeev N Deshpande; Leena Deshpande (Indian Journal of Plastic Surgery)
Hemifacial hyperplasia is a rare congenital deformity, affecting soft and bony tissues of one half of the face. The etiology of the condition is unknown and no pattern of heredity is described. A case of hemifacial hyperplasia and its management is described here.